Implementation of whole-genome and transcriptome sequencing into clinical cancer care - Cuppen, Edwin; Elemento, Olivier; Rosenquist, Richard; Nikic, Svetlana; IJzerman, Maarten; Zaleski, Isabelle Durand; Frederix, Geert; Levin, Lars-Åke; Mullighan, Charles G.; Buettner, Reinhard; Pugh, Trevor J.; Grimmond, Sean; et al. (JCO precision oncology, 2022)
PURPOSE - - The combination of whole-genome and transcriptome sequencing (WGTS) is expected to transform diagnosis and treatment for patients with cancer. WGTS is a comprehensive precision diagnostic test that is starting to replace the standard of care for oncology molecular testing in health care systems around the world; however, the implementation and widescale adoption of this best-in-class testing is lacking. - - METHODS - - Here, we address the barriers in integrating WGTS for cancer diagnostics and treatment selection and answer questions regarding utility in different cancer types, cost-effectiveness and affordability, and other practical considerations for WGTS implementation. - - RESULTS - - We review the current studies implementing WGTS in health care systems and provide a synopsis of the clinical evidence and insights into practical considerations for WGTS implementation. We reflect on regulatory, costs, reimbursement, and incidental findings aspects of this test. - - CONCLUSION - - WGTS is an appropriate comprehensive clinical test for many tumor types and can replace multiple, cascade testing approaches currently performed. Decreasing sequencing cost, increasing number of clinically relevant aberrations and discovery of more complex biomarkers of treatment response, should pave the way for health care systems and laboratories in implementing WGTS into clinical practice, to transform diagnosis and treatment for patients with cancer.
Gesehen am 26.06.2023